IMPLEMENTATION OF ISLAMIC EDUCATION AND MULTICULTURAL EDUCATION IN EDUCATORS - Hirlan Hirlan; Wahyu Stiawan (RETEL Journal (Journal on Publication of The Research on Teaching and Language), 2018)
Multicultural education as a new paradigm that comes into the world at the earliest century XX have vision and program gets things square the rising generation face global the world society in edges multicultural. Multicultural education as a program designed by gets guidance on dimensioning: content integration, knowledge construction, prejudice reduction, equitable pedagogy, and empowering school culture and social structure. Via this design, multicultural diimplementasikan's education in multicultural learning gets nationalistic point basis to result, studying subjects that has an interest: (1) get knowledges and well-informed about concept multiculturalism (knowledge); (2) have sharp-witted attitudes and able as membered as a society which multicultural (disposition); and (3) have the skills to take a decision and give alternatives to about problem multicultural in look after integration and congruity (skill). Keyword: Islamic Education, Multicultural Education